IMPLEMENTASI MODEL PROBLEM BASED LEARNING OLEH GURU AKIDAH AKHLAK GUNA MENINGKATKAN MINAT BELAJAR SISWA DENGAN MENGGUNAKAN MEDIA POWER POINT (Studi Kasus Siswa Kelas XI Di Madrasah Aliyah Negeri 1 Kubu Raya) - Muhammad Basarrudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning methods play an important role in more effective teaching learning activities, so the success of teachers in teaching pupils depends on teacher success. As a result, determining the right learning method will result in quality learning. Problem Based Learning (PBL) is a problem-solving-focused learning approach. The goal is for students to be more involved in learning. One of the subjects at school is morality, which takes a lot of time to learn.Students should be able to understand Akhlak lessons in class because they are very much related to everyday life. One of the most suitable learning models for Akhlak is the Problem Based Learning Model. This is because it allows students to learn to think critically and cultivate a collaborative attitude to solve problems and strengthen relationships. The aim is to learn how to apply problem-based learning to Akhlak lessons in MAN 1 Kubu Raya and to find out how to use PowerPoint to improve student learning interest. This research uses a descriptive qualitative approach, where data collection techniques use observations, interviews, and documentation. The results of the research showed that the problem-based learning model was applied in MAN 1 Kubu Raya for Akidah Akhlak subjects in class XI. There are three stages, namely preparation, implementation, and evaluation. Overall, it can be said that students are very interested in the Akhlak lessons taught through the Problem Based Learning model. This is because students are required to improve their ability to think critically and work together in groups to solve the problems discussed in learning. Students also have the opportunity to learn more about issues that are closely related to their daily lives.